2023
DOI: 10.1039/d3cc02169f
|View full text |Cite
|
Sign up to set email alerts
|

Semisynthetic maturation of [FeFe]-hydrogenase using [Fe2(μ-SH)2(CN)2(CO)4]2−: key roles for HydF and GTP

Batuhan Balci,
Roark D. O’Neill,
Eric M. Shepard
et al.

Abstract: Here we describe maturation of the [FeFe]-hydrogenase from its [4Fe-4S]-bound precursor state by using the synthetic complex [Fe2(μ-SH)2(CN)2(CO)4]2- together with HydF and components of the glycine cleavage system, but in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…In summary, these results indicate that syn-dimer is capable of maturating apo-hydrogenase in the defined maturation conditions and consistent with the recent defined maturation study performed using C. acetobutylicum maturase …”
Section: Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In summary, these results indicate that syn-dimer is capable of maturating apo-hydrogenase in the defined maturation conditions and consistent with the recent defined maturation study performed using C. acetobutylicum maturase …”
Section: Results and Discussionsupporting
confidence: 91%
“…We demonstrate that the syn-dimer is compatible with the defined maturation approach. Similar results were recently disclosed by Broderick and co-workers . We show that syn-B is also compatible with simplified media.…”
Section: Introductionsupporting
confidence: 92%
“…Recent results have also shown that using a synthetic [2Fe] subcluster lacking the adt bridge can lead to complete in vitro maturation of HydA in the presence of the enzyme HydF and components that generate H met . 22 These results suggest that installation of the adt bridge occurs on the enzyme HydF. The HydG product, complex B, is a diamagnetic (S = 0) low-spin Fe(II) complex and is thus undetectable by EPR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 89%
“…This dimerization results in the formation of an Fe 2 S 2 (CO) 4 (CN) 2 species needing only the addition of the CH 2 NHCH 2 component of the adt bridge to complete the binuclear subcluster. Serine and NH 4 + serve as the source of C and N, respectively, in the CH 2 NHCH 2 component and are transferred through the aminomethyl group of the lipoylated H-protein (H met ) to complete the adt bridge. ,, Semisynthetic approaches to [2Fe] H-cluster biosynthesis have shown that a synthetic version of complex B, termed Syn-B, is also capable of in vitro maturation by acting as the substrate for HydE in the absence of HydG. , This highlights the importance of the [Fe­(II)­(CN)­(CO) 2 (cysteinate)] − organometallic product structure along the maturation pathway, including preventing the release of cytotoxic CO and CN – . Recent results have also shown that using a synthetic [2Fe] subcluster lacking the adt bridge can lead to complete in vitro maturation of HydA in the presence of the enzyme HydF and components that generate H met .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation